Pengaruh Atmosfer Ritel dan Tekanan Kelompok Referensi Terhadap Nilai Hedonik dan Pembelian Impulsif - Sastradhi, Yuanna Devy; Widagda K., I.G.N. Jaya Agung (E-Jurnal Manajemen; Vol 3 No 2 (2014), 2014)
This study empirically attempts to explore the influences of retail’s atmosphere and reference group on hedonic value and impulsive purchase. Sampling method that used on this research was purposive sampling that resulted 110 respondents. The data for this study was collected by questionnaire method with path analysis as data analysis technique. The result of this study reveals that retail’s atmosphere and reference group have a positive and significant influence toward impulsive purchase. Aside of that this study also showed that retail’s atmosphere and reference group have a positive and significant influence toward impulsive purchase when mediated by hedonic value. Keywords : retail’s atmosphere, reference group, hedonic value, impulsive purchase